Optimizing PV integration using COA: power loss reduction and voltage stability under time-varying loads / Siti Salwa Mat Isa ... [et al.] - Mat Isa, Siti Salwa; Ibrahim, Mohammad Nizam; Mohamad @ Ahmad, Anuar; Dahlan, Nofri Yenita; Jamahori, Hanis Farhah; Mat Isa, Siti Sarah (UiTM Press, 2025)
The increasing use of renewable energy (RE) especially photovoltaic (PV) systems has made it essential to optimize their integration into power distribution networks, especially under time-varying load conditions. This study addresses the challenge of aligning PV generation with fluctuating load demands to reduce power losses and enhance voltage stability by analyzing the impact of multiple PV systems on industrial, residential and commercial loads within the IEEE 69-bus distribution network. The Coyote Optimization Algorithm (COA) is employed to determine the optimal location and size of PV systems. The results indicate a significant 45.9553% reduction in power loss for commercial loads with three PV systems, along with the most substantial improvement in voltage profiles compared to other load types. These findings highlight the importance of strategic PV placement and demonstrate the effectiveness of COA in enhancing network performance.